Patterns of Lip Print and Fingerprint in Gender Identification: A Cross-sectional Study - Baral, Radha; Silwal, Ganesh; Yadav, Dinesh Kumar; Koju, Sushmit; Maharjan, Nisha; Bajracharya, Dipshikha (Journal of BP Koirala Institute of Health Sciences, 2020)
Background: Personal identification is one of the key areas in the forensic sciences. A combination of different simple and easily available methods such as lip prints and fingerprints can be used for human identification. Our objective was to analyze the types of lip print and fingerprint patterns in dental students and to identify if they were associated with gender. Methods: This was a cross-sectional comparative study conducted in 150 students (male: female 1:1), aged between 17 to 34 years, from Kantipur Dental College. The lip print and fingerprint patterns were recorded and interpreted based on the Tsuchihashi and Michael Kucken classification respectively. Results: The most common lip print pattern was intersected type (44, 29.3%), while the least common was undetermined type (7, 4.7%). The intersected lip pattern (23, 30.7%) was most prevalent in males and the vertical pattern (28, 37.3%) was most prevalent in females (p < 0.05). The loop-type (82, 54.7%) fingerprint pattern was the most common while the arch-type (19, 12.7%) was the least common. The most common fingerprint pattern in both sexes was loop pattern (38, 50.7%). Conclusions: The type of lip print pattern holds potential promise as a supplementary tool for gender identification. However, fingerprint pattern was not associated with gender.